ANALISIS PENERAPAN SISTEM BUDGETING TERHADAP EFEKTIVITAS BIAYA PRODUKSI PADA UMKM TATA SNACK - Nadya Lupitasari; Sri Luayyi; Srikalimah (ICMA Nasional, 2024)
Good planning can make a company survive under any conditions. One of the planning tools in accounting records is a budgeting system. This study aims to determine and analyze the application of the budgeting system to the effectiveness of production costs during and after the Covid - 19 pandemic. This research was carried out from March to August 2023 using a comparative study technique with a qualitative approach which was carried out at UKM Tata Snack Kediri .The research results obtained are that Tata Snack UMKM has the same level of effectiveness in 2020 and 2022, which is 101%, but when viewed from the sales side, the production costs incurred by Tata Snack UMKM are more effective in 2020 with sales of IDR 1,800 ,040,000,- compared to 2022 which is IDR 1,148,180,000,-. Apart from that, there are production costs that Tata Snack must pay attention to,, namely the cost of packing with a decreasing percentage index from 2020 at 68% and 2022 at 50%.